(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India is one of the fastest developing countries in the world. In last few decades it has gone through various processes of urbanization and industrializations which is the need of the hour. However, in this process of development the Indian society has by and large ignored the cause of environmental protection. Being a developing country it has its own kinds of need and problems. Sometimes it is said that the problem of environmental degradation in India is not due to development but it’s under development. However, fact remains which India and Indians cannot deny by thousands of fictions, that it is a question of development versus environment for which Indian society has to find answers. Both the issues are crucial neither the environment can be ignored nor the development. Development is needed for social and economic progress of the country while ecology is equally crucial for providing clean and healthy environment for the citizens. This has lead to peculiar and paradoxical situation in India, while India has been identified as having the mega biodiversity geographical area but at the same time due to growing economy, environmental condition is degrading at a faster pace. Economy is growing yet a large part of the population of this country is suffering from poverty at the same time. To maintain a balance between development and environment India has also adopted the principle of sustainable development. In this paper the researcher intends to examine the how the principle of sustainable development which emerged from the international law has been adopted in India.